Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1161/01.cir.0000066690.89407.ce
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Fibrinogen Aα Thr312Ala Polymorphism

Abstract: Background-The fibrinogen A␣ Thr312Ala polymorphism occurs within the ␣C domain of fibrinogen, which is important for lateral aggregation and factor XIII-induced cross-linking of fibrin fibers. We have previously shown an association of Ala312 fibrinogen with poststroke mortality in subjects with atrial fibrillation and with pulmonary embolism in subjects with venous thrombosis. Methods and Results-We studied the properties of clots formed from purified Ala312 and Thr312 fibrinogen and found that Ala312 fibrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
105
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 18 publications
1
105
1
1
Order By: Relevance
“…65 It has been reported that the Ala312 allele is associated with more rigid and less porous fibrin gel structures. 66 Ala312 fibrin clots had thicker fibers and more extensive ␣-chain cross-linking than Thr312 clots. 66 These results suggested that Ala312 fibrin clots are more resistant to fibrinolysis, which might increase the risk for thrombosis.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…65 It has been reported that the Ala312 allele is associated with more rigid and less porous fibrin gel structures. 66 Ala312 fibrin clots had thicker fibers and more extensive ␣-chain cross-linking than Thr312 clots. 66 These results suggested that Ala312 fibrin clots are more resistant to fibrinolysis, which might increase the risk for thrombosis.…”
Section: Discussionmentioning
confidence: 87%
“…66 Ala312 fibrin clots had thicker fibers and more extensive ␣-chain cross-linking than Thr312 clots. 66 These results suggested that Ala312 fibrin clots are more resistant to fibrinolysis, which might increase the risk for thrombosis. 56 However, because this polymorphism is located on FGA-H2, which is strongly linked to FGG-H2, it is not unlikely that the risk reported to be associated with this polymorphism 67 is in fact caused by linkage with FGG-H2.…”
Section: Discussionmentioning
confidence: 87%
“…The ultrastructure of the clot demonstrates larger average fibrin fiber diameters for Ala312 clots, but with a similar number of branch points as Thr312 (Table). 62 Clinical studies have reported that the Ala allele of the Thr312Ala polymorphism predisposes to embolization in arterial and venous systems. There is an association of the Ala allele with poststroke mortality in subjects with atrial fibrillation.…”
Section: A␣ Thr312ala Polymorphismmentioning
confidence: 99%
“…64 It may be possible that stiffer clots as observed in vitro are more brittle and tend to fragment more easily. 62 …”
Section: A␣ Thr312ala Polymorphismmentioning
confidence: 99%
See 1 more Smart Citation